The Effects of Globalization on Working Conditions in Developing Countries : An Analysis Framework and Country Study Results - Jayasuriya, Ruwan (World Bank, Washington, DC, 2012)
Globalization defined as falling barriers to, and the increase in, trade, migration, and investment across borders directly affects workers in both developed and developing countries. While most global trade and investment is between the developed countries, globalization has increased dramatically in a number of developing countries. Understanding the effects of globalization is critical for governments concerned about employment, working conditions, and, ultimately, poverty reduction. Broadly defined, working conditions include wages and other key job characteristics including (but not necessarily limited to) health and safety, hours, security, benefits, and representation. These conditions have direct and indirect effects on the risk of falling or staying in poverty. This note outlines an approach for a systematic cross-country comparison of the relationship between globalization and working conditions. In addition, the results from applying this approach to five countries (Cambodia, El Salvador, Honduras, Indonesia, and Madagascar) are presented. The country study results described in this note support the hypothesis that globalization has contributed to a shift of workers from sectors with low wage and poor non-wage working conditions (i.e., agriculture) to sectors with relatively higher wages and better non-wage working conditions.